A Dopamine-Responsive Signal Transduction Controls Transcription of Salmonella enterica Serovar Typhimurium Virulence Genes - Dezhi Yang (American Society for Microbiology, 2019)
ABSTRACT We have shown that the ligand-responsive MarR family member SlyA plays an important role in transcription activation of multiple virulence genes in Salmonella enterica serovar Typhimurium by responding to guanosine tetraphosphate (ppGpp). Here, we demonstrate that another MarR family member, EmrR, is required for virulence of S. Typhimurium and another enteric bacterium, Yersinia pestis. EmrR is found to activate transcription of an array of virulence determinants, including Salmonella pathogenicity island 2 (SPI-2) genes and several divergent operons, which have been shown to be activated by SlyA and the PhoP/PhoQ two-component system. We studied the regulatory effect of EmrR on one of these genetic loci, i.e., the pagC-pagD divergent operon, and characterized a catecholamine neurotransmitter, dopamine, as an EmrR-sensed signal. Dopamine acts on EmrR to reduce its ability to bind to the target promoters, thus functioning as a negative signal to downregulate this EmrR-activated transcription. EmrR can bind to AT-rich sequences, which particularly overlap the SlyA and PhoP binding sites in the pagC-pagD divergent promoter. EmrR is a priming transcription regulator that binds its target promoters prior to successive transcription activators, by which it displaces universal silencer H-NS from these promoters and facilitates successive regulators to bind these regions. Regulation of the Salmonella-specific gene in Escherichia coli and Y. pestis reveals that EmrR-dependent regulation is conserved in enteric bacteria. These observations suggest that EmrR is a transcription activator to control the expression of virulence genes, including the SPI-2 genes. Dopamine can act on the EmrR-mediated signal transduction, thus downregulating expression of these virulence factors. IMPORTANCE In this study, MarR family regulator EmrR is identified as a novel virulence factor of enteric bacteria, here exemplified by Salmonella enterica serovar Typhimurium and Yersinia pestis. EmrR exerts an essential effect as a transcription activator for expression of virulence determinants, including Salmonella pathogenicity island 2 genes and a set of horizontally acquired genetic loci that formed divergent operons. EmrR senses the neurotransmitter dopamine and is subsequently released from target promoters, resulting in downregulation of the virulence gene expression. Through this action on EmrR, dopamine can weaken Salmonella resistance against host defense mechanisms. This provides an explanation for the previous observation that dopamine inhibits bacterial infection in animal gastrointestinal tracts. Our findings provide evidence that this neurotransmitter can modulate bacterial gene expression through interaction with virulence regulator EmrR.